Development Of Smart M3d Media (Simulated Media Augmented Reality Technology Mathematics 3 Dimensions) To Improve Creative Thinking In Elementary Schools - Khoirun Nikmah; Toto Nusantara; Slamet Arifin (UNIVERSITAS PAKUAN, 2026)
Creative thinking skills are essential for students because they can help them find innovative solutions in facing various challenges and problems that arise due to technological advances and their readiness in 21st century skills. This study aims to develop SMART M3D learning media to improve students' creative thinking skills in the fifth grade elementary school spatial structure material. The development model used is Lee & Owens. The validity test results show that the media meets the very valid category, with scores: media experts 90%, material experts 93%, and learning experts 94.6%. Thus, SMART M3D media is declared suitable for use in learning activities. This AR-based learning media is also considered very practical to use in the learning process. This is evidenced by the results of the teacher response questionnaire with a score of 98% and the student response questionnaire which obtained a score of 95%, both of which are included in the very practical category. Analysis of the results of the pre-test and post-test of creative thinking skills in the experimental class shows an increase in each indicator of creative thinking. The average pre-test score was 52.25 (quite creative category), increasing in the post-test to 69.25 (creative category).